PENGEMBANGAN MEDIA KARTU DOMINO BERBANTUAN AUGMENTED REALITY (AR) PADA PEMBELAJARAN BAGIAN TUBUH TUMBUHAN - Azkia Aulia Syafitri; Yuyun Elizabeth Patras; Suci Siti Lathifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to produce a product in the form of domino card media assisted byAugmented Reality (AR) in learning plant body parts in class IV SDN Cimanggu 01with 34 students. This research uses the Research and Development (RnD)research method with the ADDIE model (Analysis, Design, Development,Implementation, and Evaluation). This research begins with analyzing theproblems, curriculum, and characteristics of students, then making productdesigns, developing products, then validating products with expert validators whoare qualified in their fields, followed by conducting limited trials with respondentsand conducting an overall evaluation. The results of the product validation test getan average score of 93.33%, so the product is very feasible to use. The N-Gaintest results get an average value of 0.60 so that the product is proven to increasestudents' understanding of material with the criteria “Moderate” and the N-Gaintest results also get a percentage of 60% so that the learning process after usingthe product runs “Quite Effective”, and the results of the response of students andteachers reach 95%, so the product is very good to use.